KAJIAN EFEK SAMPING ANTIDEPRESAN TERHADAP FUNGSI SEKSUAL - Vita Manda; Amitasari Damayanti (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2022)
Depression is a mental health disorder that is a severe mood disorder characterized by the appearance of symptoms of a decrease in mood (mood), such as loss of interest, energy, concentration, and disturbances in appetite and sleep. One of the treatments for depression is the use of antidepressants. Still, sexual dysfunction has been reported as a side effect of using antidepressants, especially Selective Serotonin Reuptake Inhibitors (SSRIs), Serotonin-Norepinephrine Reuptake Inhibitors (SNRIs), and other antidepressants, namely Tricyclic Antidepressants (TCAs) have also been reported. ).Â Research resultsÂ on the side effects of using antidepressant drugs have been reported to have decreased sexual arousal and impaired orgasm (orgasm development). There are side effects that occur in the use of SSRI, SNRI, and TCA antidepressants on sexual function